The impact of walking speed on the effects of functional electrical stimulation for foot drop in people with multiple sclerosis. (17th August 2016) - Miller, L.; Rafferty, D.; Paul, L.; Mattison, P.
Abstract: Purpose : Functional electrical stimulation (FES) is effective in assisting people with multiple sclerosis (pwMS) with gait. Previous studies have investigated the effects of FES in pwMS with slow self-selected walking speeds (SSWS). This study reports on the effect of the Odstock Dropped Foot Stimulator (ODFS) on the speed and oxygen (O2 ) cost of gait in pwMS walking at a range of SSWS. Methods : Twenty pwMS (mean age 50.4 ± 7.3 years) currently using FES walked at their SSWS for 5 min with and without FES. O2 cost of gait was measured using a gas analysis system, and gait speed was calculated. Data were analysed for all participants, and comparisons were made between those with a SSWS < and >0.8 m/s (walking speed required for community ambulation). Results : Significant improvements in the speed and O2 cost of gait were seen using FES in the group with SSWS <0.8 m/s ( n = 11, p = 0.005). When participants' SSWS >0.8 m/s, no difference in gait speed was noted, and a significant increase in O2 cost of gait using FES ( n = 9, p = 0.004) was noted. Conclusion : FES has a different effect on the speed and O2 cost of gait dependent on the SSWS of pwMS. This requires further investigation. Implications for Rehabilitation: Functional electrical stimulation (FES) used for foot drop is effective in improving the speed and oxygen cost of walking in pwMS walking at SSWS <0.8 m/s. FES does not seem to have a beneficial effect on the speed and oxygen cost of walking in pwMS walking at SSWS >0.8 m/s. Further research is needed to understand the possible mechanisms involved so that FES for foot drop can be efficiently prescribed.